Constructing Optimal Portfolio From First State Investments indonesia's mutual Funds Period - Eka Putra, Chandra; Soekarno, Subiakto (Journal of Business and Management, 2013)
The goal of this thesis is to construct an optimal portfolio based on Markowitz’s modern portfolio theory from First State Investments Indonesia’s mutual funds. The time horizon of this thesis is from the beginning of 2009 until the end of 2011. There are 3 optimal portfolios that have been created. Those 3 are Maximum Return portfolio, Minimum Stadev portfolio, and Maximum Sharpe Ratio portfolio. The creation of those 3 portfolios was helped by the MS Excel Solver add-ins to determine the weights of each mutual fund in a portfolio. Then those 3 portfolios compared to each other and the market with some performance measurements like Sharpe ratio, Treynor ratio, and Jensen’s Alpha. The calculation creates a result that the best performance achieved from those 3 portfolios is the Maximum Sharpe Ratio portfolio because the portfolio generates the highest Sharpe ratio. The highest Sharpe ratio according to Markowitz is the most optimal portfolio. That portfolio exceeds the market in terms of performance with 0.0674% average daily return and 0.5640% average daily standard deviation. This thesis focuses only for the NAV of 6 First State Investments Indonesia’s mutual funds, JCI historical data, and BI rate from 2009 until 2011. The outcome of this thesis is an investment to the Maximum Sharpe Ratio portfolio which has the best performance according to Markowtiz’s modern portfolio theory among the other portfolios, mutual funds, and the market from 2009 until 2011. There are changes in the NAV, JCI’s closing prices, and BI rate to support the proposed optimal portfolio strategy. This research creates an optimal portfolio based on Markowitz’s modern portfolio theory of First State Investments Indonesia’s mutual funds for investors. Keywords: Optimal Portfolio, Mutual Fund, First State Investments Indonesia, 2009-2011.Category:Finance; Performance Management.